白首烏의 항산화 효능 및 모유두 세포의 5α-reductase mRNA 발현 억제 효능 - 조남준(Nam Joon Cho); 최영호(Young Ho Choi); 전해리(Hai Li Jeon); 이웅희(Woong Hee Lee); 김기광(Kee Kwang Kim); 한효상(Hyo Sang Han) (동의생리병리학회지, 2017)
Hair loss affects interpersonal relationships and causes psychological stress. In this study, we investigated the antioxidant activity of Cynanchi Wilfordii Radix (CWR) and its effects on dermal papilla (DP) cells. Antioxidant efficacy was examined by ABTS assay. To confirm the effect on cell activity, MTS assay was performed and cell count was directly measured by hemocytometer. The mRNA expression of genes involved in hair formation and hair loss formation was confirmed by quantitative RT-PCR. CWR has a strong antioxidant activity. Cell viability of DP cells was increased to 118.5% by treatment of 0.5 mg/ml CWR for 24 hours, but the effect on the cell number was insignificant. These results suggest that CWR increases mitochondrial activity without promoting cell proliferation. Treatment of DP cells with 0.5 mg/ml CWR resulted in 48.5% reduction of mRNA expression of type 2 5α-reductase, a major cause of male hair loss. In addition, mRNA expression of bone morphogenetic pretein (BMP), fibroblast growth factor (FGF)7, and FGF10, which are closely related to hair growth, was also decreased. Reactive oxygen species (ROS) acts as a cause of hair loss. The excellent antioxidant efficacy of CWR is thought to be able to effectively remove ROS. The dihydrotestosterone produced by type 2 5α-reductase in DP cells is a potent inducer of male pattern hair loss. The inhibitory effect of type 2 5α-reductase mRNA on DP cells induced by CWR may induce a positive therapeutic effect of male pattern hair loss. KCI Citation Count: 0